First-line therapy with moderate dose capecitabine in metastatic breast cancer is safe and active: results of the MONICA trial - Kaufmann, Manfred; Maass, Nicolai; Costa, Serban-Dan; Schneeweiss, Andreas; Loibl, Sibylle; Sütterlin, Marc; Schrader, Iris; Gerber, Bernd; Bauer, Wolfgang; Wiest, Wolfgang; Tomé, Oliver; Distelrath, Andrea; et al. (European journal of cancer, 2010)
BACKGROUND: To determine activity and safety of capecitabine at a moderate dose of 2000 mg/m(2) as first-line therapy for metastatic breast cancer. - METHODS: In this prospective phase II trial, patients with HER2-negative metastatic breast cancer received first-line capecitabine 2000 mg/m(2) on days 1-14 every 3 weeks. The primary aim was to exclude a time to progression (TTP) <6 months. Secondary end-points were overall response rate, overall survival (OS), toxicity and quality of life. - RESULTS: Median age of the 161 included patients was 65 years. Median TTP and OS were 7.3 months [95% (confidence interval) CI: 6.2-8.4] and 17.1 months (95% CI: 14.0-20.3), respectively. An overall response rate of 26.1%, including 13 complete remissions was observed. Patients developing grade I-III hand-foot syndrome had a significantly longer TTP and OS and patients >65 years also achieved a significantly longer TTP. Haematological grade I-IV toxicities were leucopenia (64.0%), anaemia (50.9%) and thrombocytopenia (28.0%). Relevant non-haematological toxicities were hand-food-syndrome (37.3%), fatigue (34.2%), nausea (29.8%) and diarrhoea (20.5%). Quality of life assessment revealed an improved emotional function, but worsening of nausea and vomiting from cycle 1-10. - CONCLUSIONS: Capecitabine at a dose of 2000 mg/m(2) is active and safe as first-line treatment of patients with metastatic breast cancer.